2015
DOI: 10.1016/j.cell.2015.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous tRNA-Derived Fragments Suppress Breast Cancer Progression via YBX1 Displacement

Abstract: SUMMARY Upon exposure to stress, tRNAs are enzymatically cleaved, yielding distinct classes of tRNA-derived fragments (tRFs). We identify a novel class of tRFs derived from tRNAGlu, tRNAAsp, tRNAGly, and tRNATyr that, upon induction, suppress the stability of multiple oncogenic transcripts in breast cancer cells by displacing their 3′UTRs from the RNA-binding protein YBX1. This mode of post-transcriptional silencing is sequence-specific, as these fragments all share a common motif that matches the YBX1 recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
802
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 685 publications
(846 citation statements)
references
References 35 publications
(44 reference statements)
21
802
2
1
Order By: Relevance
“…As many studies have suggested different functions of tRFs, 8 , 9 , 11 , 28 , 36 , 37 we performed northern blotting to check whether the overexpression of tRNA Leu would generate corresponding fragments. We used 30-bp radioactive probes to detect the 3 mature isoacceptors of tRNA Leu as well as their 3′ and 5′ end-derived fragments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As many studies have suggested different functions of tRFs, 8 , 9 , 11 , 28 , 36 , 37 we performed northern blotting to check whether the overexpression of tRNA Leu would generate corresponding fragments. We used 30-bp radioactive probes to detect the 3 mature isoacceptors of tRNA Leu as well as their 3′ and 5′ end-derived fragments.…”
Section: Resultsmentioning
confidence: 99%
“…49 These new roles of tRNAs have been observed in prokaryotes as well as eukaryotes, and they are involved in various cellular phenomena, including haeme and chlorophyll biosynthesis, antibiotic cellular permeability, energy metabolism, amino acid biosynthesis and protein degradation, reverse transcription of viruses, cell apoptosis and survival, and cancer progression. 4-6 , 10 , 37 , 50-55 In this study, we investigated the novel functions of tRNAs, especially tRNA Leu , which promoted cell proliferation via RSK/MSK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…32,[63][64][65] The resulting fragments have been demonstrated to bind and inhibit translation machinery, 66 as well as bind and destabilize mRNAs directly. 67 In mouse epidermal stem cells, the expression level of the RNA m 5 C methyltransferase NSUN2 is low but increases over the course of differentiation. This occurs with a concomitant increase in protein translation that is, counter intuitively, not correlated with increased proliferation.…”
Section: Trnamentioning
confidence: 99%
“…Deletion of NSUN2 results in tRNA hypomethylation, accumulation of tRNA fragments, and reduced translation, favoring the stem cell state. 67 By this mechanism, loss of NSUN2 enhances the self-renewal of stem cells in a tumor setting as well, but it renders them sensitive to stress because they are unable to activate stress response pathways that require tRNA methylation. How tRNA fragments influence cell biology more broadly remains to be worked out.…”
Section: Trnamentioning
confidence: 99%
See 1 more Smart Citation